A Stable Conversion and Alloying Anode for Potassium‐Ion Batteries: A Combined Strategy of Encapsulation and Confinement. (20th May 2020) - Wang, Shijian; Xiong, Pan; Guo, Xin; Zhang, Jinqiang; Gao, Xiaochun; Zhang, Fan; Tang, Xiao; Notten, Peter H. L.; Wang, Guoxiu
Abstract: Potassium‐ion batteries based on conversion/alloying reactions have high potential applications in new‐generation large‐scale energy storage. However, their applications are hindered by inherent large‐volume variations and sluggish kinetics of the conversion/alloying‐type electrode materials during the repeated insertion and extraction of bulky K + ions. Although some efforts have been focused on this issue, the reported potassium‐ion batteries still suffer from poor cycling lifespans. Here, a superior stable antimony selenide (Sb2 Se3 ) anode is reported for high‐performance potassium‐ion batteries through a combined strategy of conductive encapsulation and 2D confinement. The Sb2 Se3 nanorods are uniformly coated with a conductive N‐doped carbon layer and then confined between graphene nanosheets. The synergistic effects between conductive coating and confinement effectively buffer the large volumetric variation of the conversion/alloying anodes, which can maintain structural stability for superior cyclability. The as‐prepared anodes exhibit a high reversible specific capacity of ≈590 mA h g −1 and outstanding cycling stability over 350 cycles. In situ and ex situ characterizations reveal a high structural integration of the large‐volume‐change Sb2 Se3 anodes during a reversible K storage mechanism of two‐step conversion and multistep alloying processes. This work can open up a new possibility for the design of stable conversion/alloying‐based anodes for high‐performance potassium‐ion batteries. Abstract : A combined strategy of conductive encapsulation and 2D confinement is developed to design stable conversion/alloying‐type electrode materials for potassium‐ion batteries (PIBs). When applied as anodes for PIBs, the Sb2 Se3 ‐based composite exhibits high specific capacities and excellent cycling performance. The high structural stability and reversible conversion and alloying mechanism of the composite anode are demonstrated by in situ and ex situ characterizations.